Personality and intentional binding: an exploratory study using the narcissistic personality inventory - Hascalovitz, Ann (Chen); Obhi, Sukhvinder S. (Frontiers in Human Neuroscience, 2015)
When an individual estimates the temporal interval between a voluntary action and a consequent effect, their estimates are shorter than the real duration. This perceived shortening has been termed ‘intentional binding’, and is often due to a shift in the perception of a voluntary action forward towards the effect and a shift in the perception of the effect back towards the action. Despite much work on binding, there is virtually no consideration of individual/personality differences and how they affect it. Narcissism is a psychological trait associated with an inflated sense of self, and individuals higher in levels of subclinical narcissism tend to see themselves as highly effective agents. Conversely, lower levels of narcissism may be associated with a reduced sense of agency. In this exploratory study, to assess whether individuals with different scores on a narcissism scale are associated with differences in intentional binding, we compared perceived times of actions and effects (tones) between participants with high, middle, and low scores on the Narcissistic Personality Inventory (NPI). We hypothesized that participants with higher scores would show increased binding compared to participants with lower scores. We found that participants in our middle and high groups showed a similar degree of binding, which was significantly greater than the level of binding shown by participants with the lowest scores. To our knowledge, these results are the first to demonstrate that different scores on a personality scale are associated with changes in the phenomenological experience of action, and therefore underscore the importance of considering individual/personality differences in the study of volition. Our results also reinforce the notion that intentional binding is related to agency experience.